The meaning of difference : - Rosenblum, Karen E. (McGraw-Hill, 2006)
The Meaning of Difference is a text-reader about the social construction of difference as it operates in American formulations of race, sex and gender, social class, and sexual orientation. The book is based on the conviction that similar processes are at work in the construction of differences of color, sex and gender, class, and sexuality and that these processes likely also apply to other master statuses such as disability. Four framework essays provide the conceptual structure for the book. Following each framework essay is a set of readings that illustrate the concepts and processes described in the essays. The readings have been selected for readability, conceptual depth, and applicability to a variety of statuses.